Penerapan Model Pembelajaran Discovery Learning untuk Meningkatkan Motivasi dan Hasil Belajar Fisika Peserta Didik Kelas XI IPA 3 SMAN 6 Pekanbaru Semester Genap - Lasma Br Hotang (Faculty of Science and Education, UIN Walisongo Semarang, 2019)
Knowledge obtained by students in the class only survived for a while and were unable to relate the subject matter to real life. The procedure for classroom action research uses 2 cycles and the end of each cycle is repeated daily to see the increase in motivation and learning outcomes. Students' learning motivation find from the questionnaire given at the end of the cycle. The results of the analysis showed the average of daily tests in the first cycle was 65.11 with a sufficient category; 14 students complete (38.88%) and 22 students have not yet completed (61.11%) and in the second cycle 78.77 in good categories; 33 students complete (91.7%) and 3 students have not yet finished (8.3%). The results of the questionnaire analysis showed students were motivated to the lessons, as evidenced by the average response value of more than 70%. Based on the results of the study it can be concluded that discovery learning models can increase the motivation and physical learning outcomes for students of class XI IPA 3 of SHS 6 Pekanbaru.